A Novel Service Composition Optimization Strategy. (October 2020) - Xiang, Guanjie; Tang, Jine; Qiu, Bo; Guo, Dongjiao; Li, Mengci; Zhang, Yuxin
Abstract: In order to cope with the increasingly complex application requirements, sensors work in a cooperative and collective manner. Service-oriented Wireless Sensor Networks (WSNs)frameworkbecomes an effective strategy to solve the cooperative work of sensors. Aiming at the key service composition optimization problem under this framework, this paper proposes a novel multi-channel directed harmony search algorithm (MDHS) algorithm after analyzing the performance of ant colony optimization (ACO), genetic algorithm (GA) and particle swarm optimization (PSO) algorithms on this problem. Based on harmony search algorithm (HS) algorithm, this algorithm adopts multi-channel, dynamic parameters, directional perturbation and other technologies, which greatly improves the excellence of service composition and solution efficiency. Extensive experiments have been carried out and the results show that our technique performs better than GA and PSO on reducing energy consumption and extending the life of the wireless sensor network.